Cerebral Blood Flow Velocities in Hypotensive Extremely Low Birth Weight Infants and Normotensive Infants - Lightburn, Marla H. (2009)
OBJECTIVE: To determine if hypotensive extremely low birth weight (ELBW) infants have similar cerebral hemodynamics when compared with normotensive controls. We hypothesized that hypotensive and normotensive ELBW infants have similar cerebral blood flow (CBF) velocity. STUDY DESIGN: In this case–control study, CBF velocity (using Doppler ultrasound), PCO(2), and mean arterial blood pressure (MABP) were continuously monitored twice daily prior to intensive care procedures. If an infant became hypotensive (MABP ≤ gestational age in weeks), additional monitoring was performed for 10–20 minutes, prior to treatment with dopamine. Thirty ELBW infants were enrolled (637 ± 140 g, 24.2 ± 1.1 weeks); 15 were hypotensive and 15 were gestational age/birth weight-matched normotensive controls. CBF velocity was compared using the Mann-Whitney U test. RESULTS: The groups did not differ significantly in gestational age, birth weight, race, sex, PCO(2), Apgar scores, or occurrence of severe intraventricular hemorrhage. There was no difference in mean CBF velocity (P = .934) in hypotensive infants (MABP: 23 [20–24.9] mm Hg) compared with normotensive infants (MABP: 32.6 [27.5–35.7] mm Hg). CONCLUSION: Despite being hypotensive, ELBW infants (prior to treatment), had similar CBF velocity compared with normotensive controls. Based on these results, hypotension may not indicate decreased CBF.